Innovation and competitiveness: A case study in the accounting department of an entrepreneurial-based university - Wirawan ED Radianto; Tommy Christian Efrata (Proceedings of AICS - Social Sciences, 2017)
Innovation is the most important and the most strategic aspects both for profit and non-profit companies. Innovation is an essential requirement to improve organization’s competitiveness and performance. This research is aiming to deeply explore the process of how innovation emerges in an organization so that the organization able to improve its competitiveness. This research uses an interpretative paradigm with qualitative methodology of a single case study. A single case study approach is used in the research to better explore how innovation processes emerge. The study was done in a year, with seven months of data collection. The data were obtained from a semi-structured interview methodology conducted to six full-time lecturers. Furthermore, the research was based on Miles and Huberman’s methodology to perform the data analysis. The study found that innovation can improve competitiveness. The study found three key aspects during the emergence of innovation, which are benchmarking, knowledge stock, and information. The process of innovation emerges via an interactive and intensive discussion. Interactive control system, as part of the management control, holds an important role in the process of innovation emergence. The study is as one of the references for the department of social science to create innovation.